The Enablers of CSR to Drive a Multifaceted Approach in Pakistan’s Oil and Gas Sectors - Fan Ting; Sobia Jamil; Syed Imran Zaman; Miao Miao (Symphonya, 2024)
This study intends to determine the elements for adopting corporate social responsibility (CSR) practices that would boost the organization's performance (OP) either directly or indirectly in Pakistan's oil and gas sectors. This research demonstrates how companies may improve their performance by participating in various CSR efforts, for example, companies can encourage their workers by providing them with information about CSR practices, and they can support multiple facilitators of CSR integration to enhance OP.